(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Independent learning has become an essential component of modern medical education, particularly in the study of Medical English. With the rapid development of Artificial Intelligence (AI), new opportunities have emerged for improving both learning and assessment processes. This article explores how AI-based tools can support independent learning in Medical English and enhance the accuracy, efficiency, and personalization of assessment. It also discusses the benefits, challenges, and future perspectives of integrating AI into medical language education.